2017
DOI: 10.1097/aap.0000000000000540
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ultrasound-Assisted Thoracic Epidural Placement in Patients Undergoing Upper Abdominal and Thoracic Surgery

Abstract: NCT02785055 (https://clinicaltrials.gov/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 18 publications
2
31
0
1
Order By: Relevance
“…[3][4][5][6][7] Preprocedural imaging, however, still requires blind advancement of the epidural needle and does not reduce the time or number of needle redirections required to place a thoracic epidural catheter. 8 Interest in using real-time US visualization during needle advancement to improve rates of catheter placement at the lumbar spine has recently developed. 9,10 However, this technique is difficult at the thoracic spine, given the narrow interlaminar space and steep angulation of the spinous processes, which provide poor US visibility.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] Preprocedural imaging, however, still requires blind advancement of the epidural needle and does not reduce the time or number of needle redirections required to place a thoracic epidural catheter. 8 Interest in using real-time US visualization during needle advancement to improve rates of catheter placement at the lumbar spine has recently developed. 9,10 However, this technique is difficult at the thoracic spine, given the narrow interlaminar space and steep angulation of the spinous processes, which provide poor US visibility.…”
mentioning
confidence: 99%
“…The use of pre-procedural ultrasonography for TEA catheter insertion has shown its value in postoperative analgesia in a recent study 46. Ultrasonography has shown utility in needle placement by statically (not dynamically) identifying the ligamentum flavum and dura mater.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography has shown utility in needle placement by statically (not dynamically) identifying the ligamentum flavum and dura mater. Nevertheless, catheter placement cannot be verified with this technique, which is a major limitation of this technique 4648. Furthermore, the use of the CT scan to determine catheter placement in TEA has been studied by Motamed et al who were unable to correlate the vertebral level ascertained by CT scan with a clinically assessed dermatomal level 40.…”
Section: Discussionmentioning
confidence: 99%
“…Though it has been suggested that preprocedural sonography of the thoracic spine can provide clinical benefit by defining the spinal anatomy, 11 this advantage was refuted in a recent randomized trial. 12 Doppler ultrasound has recently been shown to help visualize epidural catheters placed in the lumbar epidural space; nevertheless, efficacy of this technique has not been demonstrated in the thoracic spine. 13 Epidural waveform analysis has been used to confirm the presence of the epidural needle or catheter in the epidural space.…”
mentioning
confidence: 99%
“…Certains ont suggéré qu'une échographie de la colonne thoracique avant une procédure pouvait avoir un bénéfice clinique en précisant l'anatomie vertébrale, 11 mais cet avantage a été réfuté dans une récente étude randomisée. 12 On a aussi montré récemment que le Doppler contribuait à la visualisation des cathéters périduraux placés dans l'espace péridural lombaire; néanmoins, l'efficacité de cette technique n'a pas été démontrée au niveau thoracique. 13 L'analyse du tracé de la pression péridural a été utilisée pour confirmer la présence d'une aiguille ou d'un cathéter dans l'espace péridural.…”
unclassified